Health Information Sources, Perceived Vaccination Benefits, and Maintenance of Childhood Vaccination Schedules. Issue 11 (19th September 2019) - Hwang, Juwon; Shah, Dhavan V.
ABSTRACT: Parental concerns over the safety or necessity of childhood vaccination have increased over the past decades. At the same time, there has been a proliferation of vaccine-related information available through a range of health information sources. This study investigates the associations between evaluations of health information sources, parental perceptions of childhood vaccination benefits, and the maintenance of vaccination schedules for their children. Specifically, this study aims to (a) incorporate social media into the battery of health information sources and (b) differentiate households with a childhood autism diagnosis and those without, given unsubstantiated but persistent concerns about vaccine safety and autism. Analyzing a sample of U.S. households, a total of 4, 174 parents who have at least one child under the age of 18 were analyzed, including 138 of parents of households with a childhood autism diagnosis. Results show that the more the parents value interpersonal communication and magazines as sources of health information, the more they perceive vaccination benefits, and the more the value they put on television, the better they keep vaccination schedules up-to-date for their children. On the other hand, social media are negatively associated with their perceptions of vaccination benefits. Although parents of children diagnosed with autism are less likely to perceive vaccination benefits, no interaction effects with evaluations of health information sources are found on parental perceptions of vaccination benefits or maintenance of schedules.